Experimental evaluation of the effect of decompression on crucian carps injury during turbine passage. Issue 4 (March 2019) - Meng, L; Wang, W P; Liao, C L; Zhao, L C; Li, T Y; Zhang, H P; Ma, B Q
Abstract: A continuing environmental concern for hydropower development is the injury and mortality of fish that passes through turbines. It is well established that the rapid decompression process inside turbine passage is one of the main reasons that lead to fish injury and mortality. The knowledge of mechanisms for pressure-induced injury is required in fish-friendly turbines design. Several experiments were implemented in a specially designed pressure regulation system to simulate the pressure change in a hydraulic turbine to identify the lethal nadir pressure and lethal pressure change speed. Different sizes of Crucian Carps were tested and the results were slightly different between them. Smaller Crucian carps have higher survival rate than the larger ones during the same simulated turbine passage tests. Operations that would optimize the survival of Crucian carps, such as higher nadir pressure and slower decompression speed, were also tested to provide more details in further design works. Nadir pressure higher than a pressure value turned out to be friendlier for all sizes of Crucian Carps. The results of the experiments will be beneficial to the fish-friendly turbine design and optimization.